2020
DOI: 10.1177/0269881120936544
|View full text |Cite
|
Sign up to set email alerts
|

Trends in risky prescriptions of opioid analgesics from 2011 to 2015 in Northern Germany

Abstract: Introduction: Due to their euphoric and sedative effects, opioid analgesics have high potential for abuse and dependence. In the last decade in the USA and many Western European Countries the prescription rates of opioid analgesics have steadily increased. Objective: This study describes 5-year trends in the prescription of opioid analgesics and risk indicators such as duration, dose and ‘doctor shopping’ in Northern Germany. Methods: The annual rates of opioid analgesic prescriptions have been analysed for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In general, taking opioids in higher than the recommended doses (Häuser et al 2020) or longer than 3 months may promote substance abuse (Verthein et al 2020). Opioid abuse is a substantial problem in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, taking opioids in higher than the recommended doses (Häuser et al 2020) or longer than 3 months may promote substance abuse (Verthein et al 2020). Opioid abuse is a substantial problem in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2000 and 2010 the percentage of individuals with at least one opioid prescription per year increased from 3.3% to 4.5% among persons insured through a regional German SHI provider (Schubert et al 2013). Other studies based on data of other German SHI providers identified a less steep increase in patients with opioid prescriptions from 5.7% to 5.9% from 2006 to 2009 (Werber et al 2015) and in Northern Germany from 4.4% to 4.8% from 2011 to 2015 (Verthein et al 2020).…”
Section: Introductionmentioning
confidence: 94%
“…The use of opioid analgesics (OA) is an established component of adequate pain therapy in palliative and acute medicine for patients with severe pain (1). Over the last 25 years, an increase in OA prescriptions can be observed not only internationally in the most affected countries such as the US (2) or Canada (3), but also in Germany (4)(5)(6)(7). Based on analyses of German health insurance data, long-term prescriptions (duration ≥3 months) increased by about four percentage points between 2006 and 2015 (8).…”
Section: Introductionmentioning
confidence: 99%